Beyond sounds and words volume in honour of Janina Aniela Ozga - Niżegorodcew, Anna; Jodłowiec, Maria (Jagiellonian University Press, 2011)
The present volume is a token of gratitude for our colleague, Janina Aniela Ozga, a senior lecturer at the Institute of English Philology of the Jagiellonian University. The book is a collection of papers on a wide spectrum of topics, ranging from Hamlet to Zoolander, which reflect diverse academic interests of the authors: literary theory, linguistics, translation studies, philosophy of language, history and language teaching. The common thread running through all the papers is the desire of the authors - all of them humanists involved in academic pursuits - to place in a theoretical perspective of their discipline and shed new light on an interesting research problem in literature, art, language use or language teaching that they have identified